Odpowiedzi

2010-03-15T21:21:23+01:00
2(4-√2)(4+√2) + 2(4+√2)10 + 2(4-√2)10=
2(16-2) + 80 + 20√2 + 80 -20√2=
28 +80 +80= 188
2010-03-15T21:36:47+01:00
2(4-√2) (4+√2)+2 (4+√2)10+2(4-√2)10=
= 2[ 4² -(√2)²] + 2(4 + √2)¹⁺ + 2( 4 -√2) ¹⁺=
= 2[( 16 - 2) + (4 + √2)¹⁺ + ( 4 -√2) ¹⁺] =
= 2[ 14 + (4 + √2)¹⁺ + ( 4 -√2) ¹⁺]

Nie wiem czy za nawiasem jest do potegi 10 czy pomnożone przez 10 ?

2(4-√2) (4+√2)+2 (4+√2)10+2(4-√2)10=
= 2(16 -2) + 20(4 + √2) + 20( 4 -√2) =
= 2*14 + 80 + 20√2 + 80 - 20√2 =
= 28 +160=
= 188